APRESIASI SENI LUKIS TERHADAP PERKEMBANGAN ANAK BERKEBUTUHAN KHUSUS - ANDRIK MUSFALRI (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2017)
Fine art in Indonesia is growing quite well with Indonesian art to retain the title. In this development, the art does not look different every existing disciplines because it does not need the attitude of specialists to produce a masterpiece. With creativity honed, an art can be born without the need for attachment. The artists are free to express, sometimes tend to look to play around with experiments to produce a high-value art. Fourth view student of Institut Seni Indonesia Yogyakarta, that pure art in addition to the expression language can also provide real benefits to society, such as for example on their activities in SLB Yogyakarta, they not only appreciate about the world of children with special needs, but through their art able to give happiness, benefit personally as performers who falls spaciousness directly, that art is not pegged on acknowlege looking acknowlege collectors and art world, but art can appreciate significantly, the purpose and benefits of the artist to appreciate a problem through the arts.